Assessing CYP2C19 Ontogeny in Neonates and Infants Using Physiologically Based Pharmacokinetic Models: Impact of Enzyme Maturation Versus Inhibition. (5th December 2018) - Duan, Peng; Wu, Fang; Moore, Jason N.; Fisher, Jeffrey; Crentsil, Victor; Gonzalez, Daniel; Zhang, Lei; Burckart, Gilbert J.; Wang, Jian
Abstract : The objective of this study was to develop pediatric physiologically based pharmacokinetic (PBPK) models for pantoprazole and esomeprazole. Pediatric PBPK models were developed by Simcyp version 15 by incorporating cytochrome P450 (CYP)2C19 maturation and auto‐inhibition. The predicted‐to‐observed pantoprazole clearance (CL) ratio ranged from 0.96–1.35 in children 1–17 years of age and 0.43–0.70 in term infants. The predicted‐to‐observed esomeprazole CL ratio ranged from 1.08–1.50 for children 6–17 years of age, and 0.15–0.33 for infants. The prediction was markedly improved by assuming no auto‐inhibition of esomeprazole in infants in the PBPK model. Our results suggested that the CYP2C19 auto‐inhibition model was appropriate for esomeprazole in adults and older children but could not be directly extended to infants. A better understanding of the complex interplay of enzyme maturation, inhibition, and compensatory mechanisms for CYP2C19 is necessary for PBPK modeling in infants.